Bimodal Fluorescence/Magnetic Resonance Molecular Probes with Extended Spin Lifetimes. Issue 8 (5th January 2022) - Yang, Shengjun; Saul, Philip; Mamone, Salvatore; Kaltschnee, Lukas; Glöggler, Stefan
Abstract: Bimodal molecular probes combining nuclear magnetic resonance (NMR) and fluorescence have been widely studied in basic science, as well as clinical research. The investigation of spin phenomena holds promise to broaden the scope of available probes allowing deeper insights into physiological processes. Herein, a class of molecules with a bimodal character with respect to fluorescence and nuclear spin singlet states is introduced. Singlet states are NMR silent but can be probed indirectly. Symmetric, perdeuterated molecules, in which the singlet states can be populated by vanishingly small electron‐mediated couplings (below 1 Hz) are reported. The lifetimes of these states are an order of magnitude longer than the longitudinal relaxation times and up to four minutes at 7 T. Moreover, these molecules show either aggregation induced emission (AIE) or aggregation caused quenching (ACQ) with respect to their fluorescence. In the latter case, the existence of excited dimers, which are proposed to use in a switchable manner in combination with the quenching of nuclear spin singlet states, is observed Abstract : Long‐lived nuclear singlet states have been shown to be a viable tool in many different areas of research, from material sciences over the investigation of catalytic cycles to applications in biochemistry. The synthesis of four compounds, in which a nuclear singlet state in pairs of 13 C and 15 N nuclei can be populated is shown. Furthermore, bimodal fluorescence/singlet‐state NMR application for the determination of water concentration has been investigated, which can be useful in a variety of fields.